The Search for and Discovery of Yiddishist Women - Häll, Lina (Lietuvos istorijos studijos, 2025)
On Saulė Valiūnaitė’s Doctoral Thesis “Yiddishist Women and their Contribution to the Formation and Presentation of Secular Jewishness in the Interwar Vilna“, and its Defense
Keywords: -